Blow-up and decay of solutions for a viscoelastic Kirchhoff-type equation with distributed delay and variable exponents - Choucha A.; Boulaaras S.; Jan R.; Alharbi R. (John Wiley and Sons Ltd, 2025)
In this article, we focussed on a nonlinear viscoelastic Kirchhoff-type equation with distributed delay and variable-exponents. The blow-up solutions of the problem are proved under suitable hypothesis, and by using an integral inequality due to Komornik, the general decay outcome is obtained in the case (Formula presented.). ? 2024 John Wiley & Sons, Ltd.